Comparative Evaluation of Craniofacial Morphology between Monozygotic and Dizygotic Individuals and Zygosity determination by Microsatellites -A Dermatoglyphic Study - Varma KVV, Pratap; Bai M, Pavithra; Panda, Suchareeta; Patil, Shruti; Goutham.N, Goutham.N; kumar C, Naveen (Journal of Neonatal Surgery, 2025)
Introduction: The interplay between genetic and environmental factors in craniofacial growth and development has long been a subject of research. This study aims to evaluate craniofacial morphology differences between monozygotic and dizygotic twins and determine zygosity using microsatellites and dermatoglyphics. Materials and Methodology: A total of 33 pairs of twins (aged 16–26 years) from Chennai were analyzed. Zygosity determination was performed using microsatellites as DNA markers and fingerprint dermatoglyphic patterns. Craniofacial morphology was assessed through cephalometric analysis. Statistical evaluation was conducted using Pearson's correlation and independent t-tests. Results: Monozygotic twins exhibited a significantly higher genetic influence on vertical craniofacial parameters compared to dizygotic twins. Dermatoglyphic analysis showed that total numerical fingerprint values were more reliable in determining zygosity than ridge counts. Microsatellite markers provided a 98% accuracy rate in zygosity determination. Conclusion: This study confirms that genetic factors strongly influence craniofacial morphology, particularly vertical dimensions. Microsatellite DNA markers are a highly reliable method for zygosity determination, while dermatoglyphic patterns offer supplementary insights. The findings have important implications for Orthodontic treatment planning by identifying heritable skeletal characteristics.